Vascular endothelial growth factor (VEGF) gene polymorphism in oral submucous fibrosis subjects - A preliminary study - Rai, Devishree V; Guttal, Kruthika S; Kulkarni, Bhusan B; Hiremath, Shivaprakash; Burde, Krishna N (Asian Journal of Medical Sciences, 2016)
Background: Oral Submucous Fibrosis is one of the oral potentially malignant disorders presenting with progressive restriction in mouth opening. The condition having a high malignant transformation rate necessitates identification of biomarkers to be employed for early detection of malignant change. This will influence the prognosis in addition to adding better quality of life to patients. Aims and Objectives: To relate the association of VEGF -460C/T polymorphism in patients with OSMF and to compare the same among healthy subjects. Materials and Methods: Thirty patients with Oral submucous fibrosis and 20 controls free from habits and any form of lesions were included in the study. The polymorphism of VEGF gene was detected by polymerase chain reaction-based restriction analysis. Results: Sixty-four percent of the population in the study was in the age group of 21-40 yrs suggesting the prominence of disease in younger individuals with male predominance. With reference to polymorphism, 6.67% of the subjects from OSMF group showed CT polymorphism and 16.67% showed TT polymorphism. There were no statistically significant differences in the polymorphism between the study group and controls. However the frequency of T allele in the patient group 12 (20%) was greater than that in the control group 1 (2.5%), which was a significant finding. There was no association between the habits, frequency of habits, duration of quid placement, site of quid placement and style of chewing with the nature of polymorphism. Conclusion: VEGF 460C/T has the potential to be used as a prognostic marker in predicting the malignant transformation of OSMF. <span style="color: black; font-family: 'Verdana','sans-serif'; font-size: 6pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Asian Journal of Medical Sciences Vol.7(5) 2016 10-16